2009
DOI: 10.1128/cvi.00150-09
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Whole-Blood Gamma Interferon Assay for Detection of Mycobacterium bovis -Infected Cattle

Abstract: Antigens of Mycobacterium bovis elicit a cell-mediated immune response upon intradermal injection in cattle.In vitro, such antigens stimulate the production of gamma interferon (IFN-␥) by bovine T cells in whole-blood culture (IFN-␥ assay). We have analyzed various parameters of the in vitro IFN-␥ assay, ranging from blood sampling to execution of the IFN-␥ test, in view of potential simplifications of the assay. Here, we show that IFN-␥ responses may be reduced under certain animal handling/holding conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 12 publications
1
45
1
Order By: Relevance
“…The outbreaks of this disease have been a major cause of economic losses to livestock industries worldwide [10]. The inactive FMD vaccines are widely [7,8,11,12]. Schiller et al [8] reported that the time and temperature of culture will affect the result of assay, and the stimulation temperature needs to be 33 °C or higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outbreaks of this disease have been a major cause of economic losses to livestock industries worldwide [10]. The inactive FMD vaccines are widely [7,8,11,12]. Schiller et al [8] reported that the time and temperature of culture will affect the result of assay, and the stimulation temperature needs to be 33 °C or higher.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ release in IFN-γ assay is affected by different conditions, such as the time and temperature of blood sample storage, the time of test culture, and the kind of anticoagulant used for blood collection [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies suggested that this sensitivity benefit in relation to tuberculin and ESAT-6/CFP-10 could largely be realized only in freshly sampled blood, whilst it was less potent in blood that was stored overnight before the blood cultures were established (Vordermeier, unpublished data). This is was mainly due to the fact that overnight blood storage significantly improved the tuberculin specificity whilst it impacted less on sensitivity (Schiller et al, 2009). As now the routine application of the Bovigam assay in GB is based on blood stored overnight, further studies were needed to improve ESAT-6 and CFP-10 sensitivity in this testing scenario (see next paragraph).…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…Briefly, results in cattle have shown that the most effective vaccination strategy against bovine TB is based on priming the immune system with BCG followed by boosting with subunit vaccines containing protective antigens that are present in BCG (heterologous prime-boost strategy), DNA (Skinner et al, 2003;, protein , or viral subunit vaccines (Vordermeier et al, 2006b; Vordermeier et al, 2004;Vordermeier et al, 2009). Nevertheless, all these strategies resulted in at least a proportion of animals becoming tuberculin-test positive (both in tuberculin skin and IFN-!…”
Section: Development Of Cattle Tb Vaccinesmentioning
confidence: 99%
“…Beyond this time limit, the IFN-␥ response diminishes and signal strength (optical density [OD]) decreases and thus reduces test sensitivity and specificity (10). This narrow time window has limited the wider application of the IFN-␥ assay in tuberculosis control programs in remote areas where long transit times between collection and laboratory analysis can lead to delays in sample processing.…”
mentioning
confidence: 99%